Penggunaan Media Big Book dalam Meningkatkan Kemampuan Membaca Anak Tunagrahita Kelas VI SLB Negeri Amurang - Olie Melie Grace Merentek (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study started from observations that researchers carried out at school, that there were mild mentally retarded children who had problems in reading, especially reading syllables and words, for example reading the word parts of the child's body having problems such as the eyes, eyebrows, feet, fingers, cheeks, and teeth. . Learning to read can use big books because big books have pictures and basically mild mentally retarded children tend to learn with what they see will be their learning experience. This study aims to determine the effect of using big book media on improving early reading skills in mild mentally retarded students in class VI SLB Negeri Amurang. This research is a single subject research (Single Subject Research). The subject in this study was one child with mild mental retardation in class VI SLB Negeri Amurang. The study was conducted using the A1-B-A2 research design. Data collection was carried out using a preliminary reading ability test and observation. Data analysis is in the form of analysis under conditions and analysis between conditions. The results showed that there was a positive effect of using Big Book media on early reading skills. It is shown by data that overlaps in the analysis between conditions B/A1 and A2/A1 of 0%, which means that the smaller the percentage of overlap, the greater the influence on the target behavior. This is also supported by an increase in reading ability scores obtained by children during the baseline-1, intervention, and baseline-2 phases.